The effect of insecticides on pollinating weevils, Elaeidobius kamerunicus on flower visitation and newly-developed weevils - Su, Chong Ming; King, Jie Hung; Ong, Kian Huat (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
Overuse of insecticide could be detrimental to pollinators and reduce pollination efficiency. This study evaluated the effect of four commercial insecticides on oil palm pollinating weevil, Elaeidobius kamerunicus, with special focus on flower visitation and the emergence of newly developed weevils in a seven year-old oil palm estate. In general, total number of weevils visiting the male inflorescences reduced with the use of insecticides. Visiting weevils on the spikelets of male inflorescence were confined, counted, and stored at room temperature for the emergence of new adults. The total number of visiting weevils and newly developed weevils were recorded. This study found that all insecticides tested had varying degrees of adverse effect on the number of weevils visiting oil palm male inflorescences. On average, without any insecticide application a male inflorescence would receive 43 weevils throughout the anthesis development and the flower visitation by the weevils reached its climax on the third day of anthesis. However, when treated with insecticides, noticeable reduction (49% - 83%) in flower visitation was observed, especially in Fipronil and Diflubenzuron treated plots. In Fipronil treated plot, the reduction of weevils’ flower visitation was the sharpest, 83% and the number of newly developed weevils emerged from the spent inflorescences was only 1.68±0.89 per spikelet, which is the lowest among all treatments. In the study, it was observed that both insecticides Chromafenozide and Pyridalyl were found to be friendlier to weevil and less reduction in flower visitation and newly emerged weevils was recorded. As the mode of action of Chromafenozide and Pyridalyl is different, they can be recommended to be used alternately to provide a broader defense against pest in oil palm estates to reduce risk of resistance development.